2016
DOI: 10.1111/fare.12185
|View full text |Cite
|
Sign up to set email alerts
|

Managing Stress Levels of Parents of Children with Developmental Disabilities: A Meta‐Analytic Review of Interventions

Abstract: Parents of children diagnosed with disabilities often experience elevated levels of stress compared to those parenting children without disabilities (Baker‐Ericzén, Brookman‐Frazee, & Stahmer, 2005; Tomanik, Harris, & Hawkins, 2004). This increase in stress can have a negative impact on parent well‐being (Trute & Hiebert‐Murphy, 2002) resulting in a stress‐induced dysregulation of the immune system. In their article in this issue, Gouin, da Estrela, Desmarais, and Baker found that increased levels of social su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 62 publications
(116 reference statements)
2
41
0
2
Order By: Relevance
“…The meta‐analysis of 11 studies revealed a small significant effect, favouring psychological interventions in reducing parental stress at postintervention. This finding was consistent with a previous review comprising six quasi‐experimental studies (Lindo, Kliemann, Combes, & Frank, ), which evaluated the effects of stress management interventions and other psychological interventions on stress faced by parents of children with developmental disabilities. The interventions were found to have positive effects on parental stress.…”
Section: Discussionsupporting
confidence: 91%
“…The meta‐analysis of 11 studies revealed a small significant effect, favouring psychological interventions in reducing parental stress at postintervention. This finding was consistent with a previous review comprising six quasi‐experimental studies (Lindo, Kliemann, Combes, & Frank, ), which evaluated the effects of stress management interventions and other psychological interventions on stress faced by parents of children with developmental disabilities. The interventions were found to have positive effects on parental stress.…”
Section: Discussionsupporting
confidence: 91%
“…Children in the intervention groups had higher attachment to caregivers, improved behavior, and more typical neurobiological responses to stress than did control groups (Fisher, Gunnar, Dozier, Bruce, & Pears, ). Other prevention research on behavioral parent‐training programs found parental reductions of stress among those caring for children with developmental disabilities (Lindo, Kliemann, Combes, & Frank, ). These studies suggest that the positive effects of parenting interventions may spill over to the biological systems of individuals (Ha & Granger, ).…”
Section: The Cascading Resilience Modelmentioning
confidence: 98%
“…Recent reviews make it clear that stress is a pervasive problem for almost all families of children with intellectual and developmental disabilities. 27,28 Families of children with medical complexity, such as is the case of children with classic CZS, are at even greater risk for extreme levels of stress and caregiving burdens. 10 The cumulative effect of these and other factors creates elevated risk for a variety of adverse mental health outcomes for families (anxiety, depression, stress, anger, and fatigue), all of which can affect parents' emotional well-being and ultimately have a debilitating effect on hope, optimism, physical health, and quality of life.…”
Section: Social Consequences Of Czsmentioning
confidence: 99%
“…4,9 As such, the primary focus of these interventions is on reducing parent stress and enhancing quality of life. Major approaches include attempts to strengthen informal support networks, parent support groups, counseling to reduce marital strain, coping and stress management skills, and mindfulness training, 28,41 all of which have been demonstrated to have positive effects for some parents under some circumstances.…”
Section: Providing Individualized Treatmentsmentioning
confidence: 99%